The contributions of early adverse experiences and trajectories of respiratory sinus arrhythmia on the development of neurobehavioral disinhibition among children with prenatal substance exposure. (9th June 2014) - Conradt, Elisabeth; Degarmo, David; Fisher, Phil; Abar, Beau; Lester, Barry M.; Lagasse, Linda L.; Shankaran, Seetha; Bada, Henrietta; Bauer, Charles R.; Whitaker, Toni M.; Hammond, Jane A.
Abstract: Neurobehavioral disinhibition (ND) is a complex condition reflecting a wide range of problems involving difficulties with emotion regulation and behavior control. Respiratory sinus arrhythmia (RSA) is a physiological correlate of emotion regulation that has been studied in a variety of at-risk populations; however, there are no studies of RSA in children with ND. Data were drawn from a prospective longitudinal study of prenatal substance exposure that included 1, 073 participants. Baseline RSA and RSA reactivity to an attention-demanding task were assessed at 3, 4, 5, and 6 years. ND was assessed at ages 8/9, 11, and 13/14 years via behavioral dysregulation and executive dysfunction composite measures. Greater exposure to early adversity was related to less RSA reactivity at 3 years, increases in RSA reactivity from ages 3 to 6 years, and increased behavioral dysregulation from ages 8/9 to 13/14. RSA reactivity was examined as a moderator of the association between early adversity and changes in ND. A significant Early Adversity × RSA Reactivity quadratic interaction revealed that children with decelerations in RSA reactivity exhibited increases in behavioral dysregulation, regardless of their exposure to early adversity. However, greater exposure to early adversity was related to greater increases in behavioral dysregulation, but only if children exhibited accelerations in RSA reactivity from ages 3 to 6 years. The results contribute to our understanding of how interactions across multiple levels of analysis contribute to the development of ND.